2017
DOI: 10.1039/c7cy01052d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pore topology on synthesis and reactivity of Sn-modified zeolite catalysts for carbohydrate conversions

Abstract: A range of Sn-modified MWW, MFI, MOR and Beta zeolites were prepared by a post-synthetic Sn functionalization method and their catalytic properties for sugar conversions were evaluated. The focus of this work was to understand the effect of micropore dimensions and additional mesoporosity on the Sn incorporation and on the catalytic properties. The post-synthetic approach, which involves aciddealumination of the parent zeolite followed by SnCl 4 grafting, is highly efficient for the selective incorporation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…Specifically, over the hydrophobic surface of ZIF-8 the competition between reactant and solvent molecules are in favour of the reactant, glucose. This is similar to the catalytic activity of Sn-Beta in glucose isomerisation [46,47]. The activity and selectivity of Sn-Beta is, in part, attributed to the hydrophobic nature of the Beta zeolite framework, which prevents the inhibition of active Sn sites by water molecules [48].…”
Section: Catalytic Activitysupporting
confidence: 64%
“…Specifically, over the hydrophobic surface of ZIF-8 the competition between reactant and solvent molecules are in favour of the reactant, glucose. This is similar to the catalytic activity of Sn-Beta in glucose isomerisation [46,47]. The activity and selectivity of Sn-Beta is, in part, attributed to the hydrophobic nature of the Beta zeolite framework, which prevents the inhibition of active Sn sites by water molecules [48].…”
Section: Catalytic Activitysupporting
confidence: 64%
“…The difference in van der Waals stabilization of the intermediates defined by the size and shape of zeolite pores was proposed to be the key factor for glucose to fructose isomerization activity of Sn‐modified MOR, BEA, MFI and MWW. Despite similar intrinsic reactivity of the Lewis acidic framework Sn sites in these materials, their catalytic performances drastically vary . Periodic calculations showed an increased van der Waals stabilization of the bulky carbohydrate substrates and products in narrow pores of Sn‐MFI and Sn‐MWW zeolites, which limited their ability to access the catalytic lattice Sn sites …”
Section: Confinement‐induced Reactivity and Molecular Recognition Phementioning
confidence: 99%
“…Crystals of hydrothermal Sn-Beta zeolites prepared with the use of HF as mineralizing agent have a capped bipyramidal morphology [24]. In contrast, the textural properties strictly depend on the starting H-Beta zeolite in post-treated materials [11]. SEM pictures showed that during the Sn incorporation, the small crystals of the initial H-Beta zeolite reorganized into larger round-shape crystals (Supporting Information S3.1).…”
Section: Sem Images Of the Synthesized Catalysts Inmentioning
confidence: 99%
“…PLAs represent about 10% of the raw material globally produced for bioplastics, and their production capacity is expected to grow by 50% by 2022 as a consequence of the biobased origin and biodegradability of the compounds [9]. Additional a-hydroxy esters, such as methyl vinyl glycolate (MVG) and methyl trans-2,5,6trihydroxy-3-hexenoate (THM) are formed in the sugar conversion reaction, making the process a possible source for the production of diverse polyester monomers that contains additional groups for functionalization [7,[10][11][12] ( Figure 1). Although Sn-Beta bears great potential as a catalyst for biorefineries, it has been applied only to the conversion of simple sugars, while applications to the conversion of second generation biomass components are still lacking [13].…”
Section: Introductionmentioning
confidence: 99%